Deradicalization Strategy: A Wasathiyah Curriculum for Gen Z in Islamic Boarding Schools - Mochamad Fathurrozi; Nurul Anam; Tunde Ahmed Alfabanni (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Islamic Religious Education (PAI) faces global challenges due to the infiltration of foreign ideologies that contradict Indonesian moderation values. Generation Z, deeply immersed in technology, is vulnerable to extreme religious interpretations. Previous studies have discussed Islamic moderation, but remain limited in integrating wasathiyah values into pesantren curricula that are responsive to the characteristics of Generation Z. This study aims to develop and implement a wasathiyah-based PAI curriculum at Nurul Chotib Al-Qodiri 4 Islamic Boarding School in Jember, focusing on instilling values of moderation, tolerance, and religious balance. The research uses a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and documentation, involving participants such as caretakers, administrators, teachers, and students. Data analysis was conducted interactively through reduction, presentation, and verification, with validity tested through source and method triangulation. Results indicate that the wasathiyah curriculum enhances understanding of religious moderation, critical thinking skills, and students' inclusive attitudes. The integration of values in fiqh, creed, and moral education, along with pesantren cultural practices, effectively shapes adaptive religious character. The study concludes that the wasathiyah curriculum development is relevant for Generation Z and significantly contributes to creating a harmonious and tolerant society. Continuous evaluation is necessary to ensure the effectiveness of the curriculum. Pendidikan agama Islam (PAI) menghadapi tantangan global akibat infiltrasi ideologi asing yang bertentangan dengan nilai moderasi Indonesia. Generasi Z, yang lekat dengan teknologi, rentan terhadap pemahaman agama yang ekstrem. Penelitian terdahulu telah membahas moderasi Islam, namun masih terbatas pada integrasi nilai wasathiyah ke dalam kurikulum pesantren yang responsif terhadap karakter Generasi Z. Studi ini bertujuan mengembangkan dan mengimplementasikan kurikulum PAI berbasis wasathiyah di Pondok Pesantren Nurul Chotib Al-Qodiri 4 Jember, dengan fokus pada nilai moderasi, toleransi, dan keseimbangan beragama. Penelitian menggunakan metode kualitatif deskriptif dengan pendekatan studi kasus. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, dengan partisipan pengasuh, pengurus, ustad, dan santri. Analisis data dilakukan secara interaktif melalui reduksi, penyajian, dan verifikasi data, dengan uji keabsahan melalui triangulasi sumber dan metode. Hasil penelitian menunjukkan kurikulum wasathiyah meningkatkan pemahaman moderasi beragama, kemampuan berpikir kritis, dan sikap inklusif santri. Integrasi nilai dalam pembelajaran fikih, akidah, dan akhlak serta pembiasaan kultur pesantren efektif membentuk karakter religius yang adaptif. Simpulan penelitian menyatakan bahwa pengembangan kurikulum wasathiyah relevan bagi Generasi Z dan berkontribusi signifikan terhadap terwujudnya masyarakat harmonis dan toleran. Evaluasi berkelanjutan diperlukan untuk memastikan keefektifan kurikulum.